Sonication pre-treatment for the intensified synthesis of tricaproin using acid-resin catalyst. (16th January 2022) - Bhaskar Jadhav, Harsh; Annapure, Uday
Highlights: Intensified synthesis of triglyceride of caproic acid using ultrasound pre-treatment. Key intensification benefits as higher conversion (%) in less reaction time. Reusability of acid-resin catalyst is studied to make process economical. Ultrasound pre-treatment is the best and economical strategy to achieve higher conversion (%). Abstract: In this study synthesis of triglyceride of hexanoic acid is investigated with the application of amberlyst-15 as a catalyst in a solvent free reaction mixture with pre-treatment of ultrasonic cavitation. In present research outcome of various reaction parameters like reaction temperature, loading of catalyst and molar ratio of reactant on rate of conversion of reactant is studied. Further ultrasonic pre-treatment parameters like pre-treatment time and duty cycle are studied. During study it is established that the ideal reaction conditions for the maximum conversion of reactant were molar ratio of reactant i.e., glycerol: fatty acid as 5:3, reaction temperature of 140 °C, amberlyst-15 loading of 5%. It is also established that the pre-treatment time of 25 min and 80% duty cycle gave good results. Recyclability of amberlyst-15 is established for 15 cycles of esterification reaction. The study showed that the use of ultrasonic pre-treatment and amberlyst-15 as a catalyst have beneficial effect on rate of conversion of reactant and also have an effect on reduction in reaction time to 07 h as compared to conventional synthesis of triglycerides of hexanoic acid. Maximum conversion of 96% was obtained in 07 h with ultrasonic pre-treatment and amberlyst-15.